Bank credit and housing prices in China: Evidence from a TVP-VAR Model with stochastic volatility - Xie He; Xiao Jing Cai; Shigeyuki Hamori (Journal of Risk and Financial Management, 2018)
Housing prices in China have been rising rapidly in recent years, which is a cause for concern for China's housing market. Does bank credit influence housing prices? If so, how? Will the housing prices affect the bank credit system if the market collapses? We aim to study the dynamic relationship between housing prices and bank credit in China from the second quarter of 2005 to the fourth quarter of 2017 by using a time-varying parameter vector autoregression (VAR) model with stochastic volatility. Furthermore, we study the relationships between housing prices and housing loans on the demand side and real estate development loans on the supply side, separately. Finally, we obtain several findings. First, the relationship between housing prices and bank credit shows significant time-varying features; second, the mutual effects of housing prices and bank credit vary between the demand side and supply side; third, influences of housing prices on all kinds of bank credit are stronger than influences in the opposite direction.
Keywords: 330; housing price; bank credit; housing loans; real estate development loans; TVP-VAR model